Topical Administration of Drugs Incorporated in Carriers Containing Phospholipid Soft Vesicles for the Treatment of Skin Medical Conditions - Elka Touitou; Hiba Natsheh (MDPI AG, 2021)
This review focuses on the improved topical treatment of various medical skin conditions by the use of drugs delivered from carriers containing phospholipid soft vesicles. Topical drug delivery has many advantages over other ways of administration, having increased patient compliance, avoiding the first-pass effect following oral drug administration or not requesting multiple doses administration. However, the skin barrier prevents the access of the applied drug, affecting its therapeutic activity. Carriers containing phospholipid soft vesicles are a new approach to enhance drug delivery into the skin and to improve the treatment outcome. These vesicles contain molecules that have the property to fluidize the phospholipid bilayers generating the soft vesicle and allowing it to penetrate into the deep skin layers. Ethosomes, glycerosomes and transethosomes are soft vesicles containing ethanol, glycerol or a mixture of ethanol and a surfactant, respectively. We review a large number of publications on the research carried out in vitro, in vivo in animal models and in humans in clinical studies, with compositions containing various active molecules for treatment of skin medical conditions including skin infections, skin inflammation, psoriasis, skin cancer, acne vulgaris, hair loss, psoriasis and skin aging.